Biological and rearing mother influences on child ADHD symptoms: revisiting the developmental interface between nature and nurture. (5th September 2013) - Harold, Gordon T.; Leve, Leslie D.; Barrett, Douglas; Elam, Kit; Neiderhiser, Jenae M.; Natsuaki, Misaki N.; Shaw, Daniel S.; Reiss, David; Thapar, Anita
Abstract : Background: Families of children with attention deficit hyperactivity disorder (ADHD) report more negative family relationships than families of children without ADHD. Questions remain as to the role of genetic factors underlying associations between family relationships and children's ADHD symptoms, and the role of children's ADHD symptoms as an evocative influence on the quality of relationships experienced within such families. Utilizing the attributes of two genetically sensitive research designs, the present study examined associations between biologically related and nonbiologically related maternal ADHD symptoms, parenting practices, child impulsivity/activation, and child ADHD symptoms. The combined attributes of the study designs permit assessment of associations while controlling for passive genotype‐environment correlation and directly examining evocative genotype‐environment correlation ( r GE); two relatively under examined confounds of past research in this area. Methods: A cross‐sectional adoption‐at‐conception design (Cardiff IVF Study; C‐IVF) and a longitudinal adoption‐at‐birth design (Early Growth and Development Study; EGDS) were used. The C‐IVF sample included 160 mothers and children (age 5–8 years). The EGDS sample included 320 linked sets of adopted children (age 6 years), adoptive‐, and biologically related mothers. Questionnaires were used to assess maternal ADHD symptoms, parenting practices, child impulsivity/activation, and child ADHD symptoms. A cross‐rater approach was used across measures of maternal behavior (mother reports) and child ADHD symptoms (father reports). Results: Significant associations were revealed between rearing mother ADHD symptoms, hostile parenting behavior, and child ADHD symptoms in both samples. Because both samples consisted of genetically unrelated mothers and children, passive r GE was removed as a possible explanatory factor underlying these associations. Further, path analysis revealed evidence for evocative r GE processes in the longitudinal adoption‐at‐birth study (EGDS) from biologically related maternal ADHD symptoms to biologically unrelated maternal hostile parenting through early disrupted child behavior (impulsivity/activation), with maternal hostile parenting and disrupted child behavior associated with later child ADHD symptoms, controlling for concurrent adoptive mother ADHD symptoms. Conclusions: Results highlight the importance of genetically influenced child ADHD‐related temperamental attributes on genetically unrelated maternal hostility that in turn links to later child ADHD symptoms. Implications for intervention programs focusing on early family processes and the precursors of child ADHD symptoms are discussed.